2018
DOI: 10.2109/jcersj2.17277
|View full text |Cite
|
Sign up to set email alerts
|

Seed-free hydrothermal synthesis of all-silica deca-dodecasil 3R with essential reagents

Abstract: Deca-dodecasil 3R (DDR) was synthesized hydrothermally from essential reagents, i.e., silica source (fumed silica), water, and 1-adamantanamine, without employing seed particles or any special treatments, such as microwave or ultrasonic irradiation. The variations in synthesis time, size, and morphology of DDR particles with reagent composition, fluorine addition, and hydrothermal temperature were examined. At 160°C DDR was synthesized in 1520 d. Rhombohedral, star-like, and hexagonal plate-like particles were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The good agreement of the observed and calculated angles confirmed that the rhombohedral particle consists of six {101̅1} faces ({100} faces in the rhombohedral representation) and the crystal faces A, B, and C can be indexed as (101̅1), (11̅01̅), and (011̅1̅), respectively. These crystal faces are almost parallel to the 8-membered rings, as also shown in Figure , middle. Thus, the rhombohedral crystal particles of DDR have the highest surface density of openings for the microporous channels and are the most suitable for applications in separation engineering.…”
Section: Resultsmentioning
confidence: 57%
See 3 more Smart Citations
“…The good agreement of the observed and calculated angles confirmed that the rhombohedral particle consists of six {101̅1} faces ({100} faces in the rhombohedral representation) and the crystal faces A, B, and C can be indexed as (101̅1), (11̅01̅), and (011̅1̅), respectively. These crystal faces are almost parallel to the 8-membered rings, as also shown in Figure , middle. Thus, the rhombohedral crystal particles of DDR have the highest surface density of openings for the microporous channels and are the most suitable for applications in separation engineering.…”
Section: Resultsmentioning
confidence: 57%
“…The fractions of the two twin domains were ∼0.5 and nearly equal. In an earlier report, this binary twin operation did not improve the fit well ( R = 0.093) because a hexagonal platelike particle, which additionally contains penetration twinning, was used. These observations indicate that the rhombohedral particle exhibits twinning by merohedry but is free from penetration twinning.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bai et al 49 developed an environment-friendly synthesis method to prepare DD3R crystals, in which only the silica source, a small amount of template, and a trace amount of water were used in the synthesis, without adding a toxic solvent such as ethylenediamine or the mineralizing reagent uoride. Without seeding, Kajihara et al 50 used the essential reagents, that is, a silica source, water, and 1-ADA, hydrothermally to synthesize DD3R crystals and found that the synthesis time could be signicantly reduced from 15-20 d at a hydrothermal temperature of 433 K to 5 d at a hydrothermal temperature of 473 K. Most recently, Wang et al 51 took advantage of the synergy of microwave heating and seeding to signicantly reduce the synthesis time of DD3R crystals to a few hours, and in addition, an inorganic base, such as KOH, NaOH, or LiOH, was used as a mineralizing reagent instead of ethylenediamine and uoride, which is comparatively more environment-friendly and economical. Although signicant progress in the synthesis of DD3R crystals, in terms of the synthesis time, cost, phase purity and so forth, has been made in recent years, unfortunately, most of the synthesized crystals were not uniform in morphology and size.…”
Section: Introductionmentioning
confidence: 99%